Nga Kapua Whakapipi a Tamamutu - Strength in Unity Nurturing Future Turangitukua Leaders - Bennett, Evelyn H (Auckland University of Technology, 2007)
Education is development. It helps to create choices and opportunities for people, reduce the twin burdens of poverty and diseases, and give a stronger voice in society. For nations it creates a dynamic workforce and well-informed citizens able to compete and cooperate globally - opening doors to economic and social prosperity.This study examines how a small group of students coped under conditions of adversity. It follows in the tradition of a wide body of qualitative work that has investigated ethnic minorities and their educational experiences. Much of the existing work, however, focuses on merely describing thematically and/or conceptually, what goes on. This study aims to construct an integrated conceptual understanding of how a minority group engaged in the coping process. More specifically, this study seeks to develop a substantive theory that can help explain and predict human behaviour. Grounded theory methodology was used in aid of the theory development process (Glasser and Strauss, 1967). Put simply, grounded theory is an inductive methodology that attempts to understand action from the perspective of social actors (Brooks, 1998).To uncover the coping process, the Turangitukua students and their Hapu (sub tribe) in New Zealand are used as the main data source. Two other student groups were used for comparative purposes. Data was obtained by a number of means; including interviewing, focus groups, hui (meetings), and documentary analysis. The collected data was summarised and analysed over a two- year period.This study contributes to three areas of research. First, it adds to the small but growing body of work relating to Turangitukua hapu (sub-tribe) in New Zealand. Second, it contributes to research in the area of Maori and non-Maori relationships, especially work that focuses on interaction. And finally, it adds to the formal theoretical literature on indigenous educational settings and its management.
Keywords: Ethnic minorities; Indigenous people; Maori students; Educational opportunity; Coping with adversity; Grounded theory